Breaking the Language Barrier: Exploring English Learning Difficulties among Business Students at STIE Gema Widya Bangsa - Dini Rizki Rahayu (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2026)
English proficiency plays a significant role in preparing business students for academic success and future professional communication. However, many students continue to encounter challenges in learning English, particularly within business-related contexts. This study aimed to explore and analyze the English learning difficulties experienced by business students at STIE Gema Widya Bangsa and to identify the linguistic, affective, pedagogical, and contextual factors contributing to these difficulties. The study employed an exploratory qualitative case-study design involving fifteen Management and Accounting students selected through purposive sampling. Data were collected through semi-structured interviews, classroom observations, and document analysis and were analyzed using thematic analysis. The findings revealed three major themes: students perceived English as a difficult foreign language, experienced limited speaking ability due to insufficient opportunities for meaningful practice, and demonstrated limited understanding of TOEFL materials despite showing strong motivation to improve. The results indicate that students’ learning difficulties are shaped by the interaction of limited vocabulary and business terminology, low confidence, inadequate exposure to English, and limited speaking practice. The study implies that Business English instruction should emphasize communicative learning, contextualized business vocabulary, regular speaking activities, and structured TOEFL preparation to enhance students’ academic achievement, workplace readiness, and overall English proficiency.